Thinning Practice in Coniferous Forests - Pring, N. G. (Indian Forester, 1937)
In the early days of forestry in the Punjab and the frontier factors such as inaceossibility and small staff prevented thinnings on the present scale. However, some of the finest-woods to-day are the result of past thinnings. The writer strosses the fact that heavier grades of intensity now practised were then not feasible. Shelterwood plans increased the area under thinnings, but the tendency to thin too lightly ramained until a heavier school emerged as the result of experience. The importance of Punjab Forest leaflest NO. 1(Trevor. 1931) and No. 2(Glover, 1932), which have had an excellent affect on thinning practice, is stressed. Dealing with the classification of thinnings the writer agress with gerric that "C" grade has been very widely interpreted, and, in pratice, frequently covers C/J) to the benefit of the crops. The writer also includes paragraphs on selection forest. Plantations, spacing, thinning cycle, kinds of thinnings, broad-leaved forest, research, etc., quoting well-known authorities to support his views. Concluding he pays tribute to the work of Dehra Dun and Ghoragali trained subordinates and shows that the last decade has seen a marked tendency towards heavier thinning, evolutionary rather than revolutionary, the natural sequel to experience.